HAMBATAN DARI FAKTOR SOSIAL DALAM MENYELESAIKAN STUDI PRODI SENI RUPA FBS UNP - Akmal Husada, Wisdiarman, Erwin A (Serupa The Journal of Art Education, 2013)
The purpose of this research is to get information and to describe about:the obstruction which come from college society’s factors such as family society,teacher and peers in finishing study of Prodi Pendidikan Seni Rupa FBS UNP.The subject of research is the students of Prodi Pendidikan Seni Rupa FBS UNPPadang. While the kind of research is quantitative. The instrument which is usedis obstruction questionnaire which come from family society, teacher, and peers.The source in this research is primary data which is taken directly from therespondent trough questionnaire. To analyze the data uses descriptive analysis byusing SPSS version 16,00 Program.